2020
DOI: 10.1111/pbi.13428
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of improved EPSPS gene results in field level glyphosate tolerance and higher grain yield in rice

Abstract: Glyphosate is a popular, systemic, broad-spectrum herbicide used in modern agriculture. Being a structural analog of phosphoenolpyruvate (PEP), it inhibits 5-enolpyruvylshikimate 3-phosphate synthase (EPSPS) which is responsible for the biosynthesis of aromatic amino acids and various aromatic secondary metabolites. Taking a lead from glyphosate-resistant weeds, two mutant variants of the rice EPSPS gene were developed by amino acid substitution (T173I + P177S; TIPS-OsEPSPS and G172A + T173I + P177S; GATIPS-Os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 97 publications
(135 reference statements)
5
25
0
1
Order By: Relevance
“…The transformed genes containing double substitution mutation were overexpressed in rice, which developed significantly higher tolerance to glyphosate under the control of maize ubiquitin (ZmUbi) promoter. Interestingly, the transgenic rice plants presented 17 to 19% higher grain production along with greater tryptophan and phenylalanine contents in transgenic seeds compared to their wild type [ 92 ].…”
Section: Mechanism and Approaches For Development Of Herbicide Resistant Plants/cropsmentioning
confidence: 99%
“…The transformed genes containing double substitution mutation were overexpressed in rice, which developed significantly higher tolerance to glyphosate under the control of maize ubiquitin (ZmUbi) promoter. Interestingly, the transgenic rice plants presented 17 to 19% higher grain production along with greater tryptophan and phenylalanine contents in transgenic seeds compared to their wild type [ 92 ].…”
Section: Mechanism and Approaches For Development Of Herbicide Resistant Plants/cropsmentioning
confidence: 99%
“…This result addressed our second question regarding the influences of the EPSPS transgene on dormancy of the GE crop-wild hybrid seeds, although our knowledge is still limited to confidently explain the underlying mechanisms connecting seed dormancy with the overexpressing EPSPS transgene in rice. However, we can explain the linkage between increased seed dormancy and overexpression of the EPSPS transgene well through increased tryptophan as reported by Wang et al and Achary et al [21,32] and increased IAA by Fang et al [31], both of which are supposedly responsible for seed dormancy [21,31,32,39]. Our finding perfectly agrees with the previous conclusions that overexpression of the endogenous EPSPS gene from cultivated rice enhances the performance of many fitness-related phenotypic characteristics of transgenic plants [15,21] and physiological and metabolic processes, including tryptophan, chlorophyll, and lignin syntheses [21,31,33,34].…”
Section: Overexpressing Epsps Transgene Increases Dormancy In Ge Crop-wild Hybrid Seedsmentioning
confidence: 55%
“…Probably, the overproduction of EPSPS can accelerate the biosynthesis of tryptophan and then IAA in the shikimate pathway of the GE crop-wild hybrid descendants. Previous studies reported that overexpressing the EPSPS transgene significantly increased the tryptophan content in the GE-cultivated rice seeds [32] and in the crop-weed hybrid plants derived from an EPSPS transgenic rice (O. sativa) line (EP3) crossed with four weedy rice (O. sativa f. spontanea) accessions [21]. In addition, overexpression of the same rice EPSPS transgene also significantly increased the IAA content in GE Arabidopsis plants [31].…”
Section: Overexpressing Epsps Transgene Increases Iaa Content In Ge Crop-wild Hybrid Seedsmentioning
confidence: 94%
See 2 more Smart Citations